Students' Lived Experiences in Utilizing Artificial Intelligence for Thesis Writing - Ratih, Marta Cahya; Kastuhandani, Fidelis Chosa (LPPM Institut Pendidikan Nusantara Global, 2024)
This research report investigates students' experiences using Artificial Intelligence (AI) in the thesis writing process. Data collection was carried out by means of in-depth interviews with 6 undergraduate students at Sanata Dharma University. Transcendental phenomenology was used in this research to dig deeper into how they interacted with AI and how AI influenced their thesis writing process. This research displays three emerging themes:1) AI improved students' motivation in writing a thesis, 2) AI fosters decision-making to solve problems, 3) AI promotes students’ self-confidence and shifting attitudes. This research contributes to understanding how the use of AI affects students' experiences and their thesis writing process. Further research is needed to understand the long-term impact of using AI in the thesis writing process and higher education as a whole.